2009
DOI: 10.1093/hmg/ddp581
|View full text |Cite
|
Sign up to set email alerts
|

Sym1, the yeast ortholog of the MPV17 human disease protein, is a stress-induced bioenergetic and morphogenetic mitochondrial modulator

Abstract: A peculiar form of hepatocerebral mtDNA depletion syndrome is caused by mutations in the MPV17 gene, which encodes a small hydrophobic protein of unknown function located in the mitochondrial inner membrane. In order to define the molecular basis of MPV17 variants associated with the human disorder, we have previously taken advantage of S. cerevisiae as a model system thanks to the presence of an MPV17 ortholog gene, SYM1. We demonstrate here that the SYM1 gene product is essential to maintain OXPHOS, glycogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 42 publications
5
90
0
Order By: Relevance
“…In the case of Sym1, we were able to detect two complexes of 120 and 220 kDa. These findings agree with those of a previous study that indicated the presence of Sym1 in a high-molecular-mass complex (8). As we used denaturing conditions to purify Sym1 for our electrophysiological measurements, it remains to be analyzed if unknown constituents of the detected complexes might modulate the observed channel properties.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of Sym1, we were able to detect two complexes of 120 and 220 kDa. These findings agree with those of a previous study that indicated the presence of Sym1 in a high-molecular-mass complex (8). As we used denaturing conditions to purify Sym1 for our electrophysiological measurements, it remains to be analyzed if unknown constituents of the detected complexes might modulate the observed channel properties.…”
Section: Discussionsupporting
confidence: 91%
“…Other genes associated with hepatocerebral mitochondrial DNA depletion such as POLG and DGUOK have clear roles in mitochondrial DNA synthesis and maintenance. Deletion of the yeast ortholog of MPV17 recapitulates the DNA depletion phenotype, and experiments in yeast have suggested that MPV17 may be important for anaplerosis of TCA cycle intermediates and for maintaining mitochondrial integrity during stress conditions (Dallabona et al 2010). It is important to note that P98, the residue mutated in this patient, is conserved across evolution in organisms including worms and yeast (Blakely et al 2012).…”
Section: Discussionmentioning
confidence: 83%
“…It has been suggested that MPV17 plays a role in controlling mtDNA maintenance and oxidative phosphorylation activity in mammals and yeast [12]. A dysfunctional MPV17 protein caused by MPV17 mutations impairs mtDNA maintenance and can cause mtDNA depletion.…”
Section: Defects In Mtdna Replicationmentioning
confidence: 99%